Genetic diversity, admixture, and hatchery influence in Brook Trout (Salvelinus fontinalis) throughout western New York State. Issue 13 (14th June 2019) - Beer, Stephanie Dowell; Cornett, Scott; Austerman, Peter; Trometer, Betsy; Hoffman, Thomas; Bartron, Meredith L.
Abstract: Although Brook Trout are distributed across most of eastern North America, population numbers have declined in many regions due to habitat loss, climate change, and competition with non‐native species. In New York State, Brook Trout habitat has been substantially reduced, with many areas showing complete extirpation of Brook Trout populations, predominantly in the western portion of the state. Small, fragmented populations are at risk of genetic diversity loss, inbreeding depression, and reduced fitness, leading to a greater potential for local extirpation. Genetic monitoring is a practical tool that can facilitate further conservation‐decision making regarding small populations. In this study, we used 12 microsatellite loci to examine 3, 436 sampled Brook Trout, representing 75 sites from the Allegheny, Erie/Niagara, Genesee, Oswego, Lake Ontario, and Susquehanna drainage basins throughout western New York State. Three Brook Trout hatchery strains were also genetically characterized to evaluate the degree of hatchery introgression between wild populations and hatchery strains stocked in the region. Overall, estimates of genetic diversity varied widely: Allelic richness ranged from 2.23 to 7.485, and expected heterozygosity ranged from 0.402 to 0.766. As observed for Brook Trout in other regions, we found a high degree of genetic differentiation among populations, with all comparisons except one showing significant F ST values. Hatchery introgression was found to be minimal, with estimates ranging from 1.96% to 3.10% of wild individuals exhibiting membership proportions to a hatchery strain cluster exceeding 10% ( q  ≥ 0.10). Results from this investigation can be used to prioritize management efforts for Brook Trout in western New York State and act as a baseline to monitor future population trends. Abstract : We present a genetic assessment of Brook Trout populations throughout western New York State, a region where substantial declines in Brook Trout habitat have been documented and many populations have been extirpated. In this study, we used 12 microsatellite loci to examine 3, 436 sampled Brook Trout, representing 75 sites from the six major drainage basins throughout western New York State. The results showed widely varying levels of genetic diversity, a high degree of genetic structure, and limited wild-hatchery introgression.